Transnasal Endoscopic Orbital Decompression Combined with an Enhanced Recovery after Surgery Protocol in Graves Ophthalmopathy. (16th September 2022) - Xu, Hui-Qing; Wang, Qian; Hu, Li-Li; Li, Hong; Peng, Feng
Abstract : Objective . Although enhanced recovery after surgery (ERAS) was shown to improve patients' recovery after surgery and transnasal endoscopic orbital decompression has been associated with lesser risks of postoperative complications compared to other surgical techniques in treating Graves ophthalmopathy (GO), there are currently no clinical studies on the application of ERAS in transnasal endoscopic orbital decompression. This study aimed to investigate the potential effects of combining transnasal endoscopic orbital decompression with ERAS in the treatment of GO. Methods . A retrospective analysis was performed for 5 GO patients (10 eyes) treated with transnasal endoscopic orbital decompression from January 2021 to December 2021 at the Third Affiliated Hospital of Sun Yat-Sen University. All patients underwent ERAS, and the effects of ERAS on the postoperative complications and recovery of patients were evaluated. Results . Ophthalmological examination showed that GO patients had good correction of exophthalmos after surgery combined with ERAS. Specifically, the exophthalmos reduction in subjects was 0.9–2.1 mm, with a mean reduction of 1.23 mm. In addition, a visual acuity improvement of 0.15–0.4, with an average improvement of 0.23, was also observed. Further, the Scale of Quality of Life for Diseases with Visual Impairment (SQOL-DVI) showed that, compared with before surgery, the patients' QOL was significantly improved 2 weeks after surgery. Before surgery, there were 2 patients with diplopia and blurred vision, and after postoperative adaptive exercise, the symptoms of these 2 patients disappeared after 6 months of follow-up. As for the other 3 patients, they had no diplopia or blurred vision after surgery. Conclusion . This observational study found that transnasal endoscopic orbital decompression might be effective in treating GO, and ERAS might be considered an important adjunct to improving perioperative care and postoperative recovery.